Viabilidad de Acanthamoeba castellanii frente a virus nucleocitoplasmáticos de ADN de gran tamaño - Freire González, Claudia Elizabeth (2024)
Giant viruses (GV) are ubiquitous, just like their hosts. The recognition of Acanthamoeba castellanii’s as the laboratory host of excellence for GM identification is a tool to investigate yet unexplored GM ecosystems, which consists in recognizing the viability of amoeba against a possible viral infection. This research developed axenic cultures of Acanthamoeba castellanii diluted and monoxenic cultures of Acanthamoeba castellanii with environmental inoculums suspected of GM from the lagoons of Daniel Álvarez, Jipiro, Punzara and Carigán, belonging to the city of Loja, Ecuador. Inoculations of environmental samples were performed in three different concentrations (1:1, 1:10, 1:20) in triplicate. Infection curves were made for the number of cells with cytopathic effects (CPE) recorded from time-lapse microscopy (148h) and statistical analysis (MDS) imaging. The CPEs recorded in this study were compared with those of published studies to determine potential infective GVEs. Thus, it was possible to obtain active strains of diluted axenic cultures with a spatial arrangement that subsequently to the generation of monoxenic cultures, allowed the capture of microscopic images and identification of CPE. The 1:1 and 1:10 environmental inoculum were not significantly different, whereas the 1:20 did. The treatments of the Jipiro, Carigán and Punzara lagoons showed detachment of the monolayer, decrease in size, rounding of cells and vacuoles and cell lysis due to the possible presence of Mimivirus; while the treatments of the Daniel Álvarez Burneo lagoon also showed cell clusters, due to the suspected presence of Tupanvirus. Thus, it is concluded that the viability of Acanthamoeba castellanii was compromised differentially from the inoculated environmental samples, of which different CPEs were visualized caused by the interaction between amoebas and possibly GV.